High-intensity focused ultrasound in prostate cancer: Today's outcomes and tomorrow's perspectives. (June 2012) - Palermo, Giuseppe; Pinto, Francesco; Totaro, Angelo; Miglioranza, Eugenio; Calarco, Alessandro; Sacco, Emilio; Daddessi, Alessandro; Vittori, Matteo; Racioppi, Marco; Dagostino, Daniele; Gulino, Gaetano; Giustacchini, Mario; et al.
Abstract High-intensity focused ultrasound (HIFU) is a minimally invasive therapy applied for prostate cancer that capitalizes on the coagulation necrosis that occurs at temperatures greater than 60°C. Owing to a lack of long-term follow-up data the procedure is still considered experimental treatment. As primary therapy, HIFU is indicated in patients aged ≥70 years with clinical organ-confined disease, although it has also been used, with encouraging results, as first line salvage therapy after definitive treatment, and in locally advanced (T3–4) and non-metastatic hormone-resistant prostate cancer. Morbidity associated with this treatment method appears to be low and includes urinary retention (1–9%), urethral stricture (4–14%), incontinence (1–15%), erectile dysfunction (13–53%) and rectourethral fistulae (0–3%). The risk of complications increases with repeated treatments. A few studies have recently been published on HIFU as focal therapy. HIFU technology can be enhanced using means such as ultrasound microbubble contrast agents for assessment of therapy efficacy, magnetic resonance imaging to guide the enhancement of heat rate, and localized drug and gene delivery.